2012
DOI: 10.1007/698_2012_153
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Emerging Organic Contaminants by Composting

Abstract: Sewage sludge is a rich source of organic matter and nutrients, which can be utilized for soil improvement and plant growth. The utilization of sewage sludge for plant growth and conversion of sludge into renewable resource is often restricted by the presence of hazardous organic matter (HOM) including di-(2-ethylhexyl) phthalate (DEHP) and antibiotics. HOM enters the sewerage system through various domestic and industrial sources; they are mostly hydrophobic in nature and recalcitrant to microorganisms. HOM h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…For chemical emerging pollutants, Kumar (2013) showed that composting was an effective method for the mineralization and treatment of di-(2-ethyl hexyl) phthalate (DEHP) in sewage sludge that could otherwise be harmful to the environment. The author identified a need for further research to understand the exact mechanism by which organic material is degraded during composting.…”
Section: Enhanced Natural Systemsmentioning
confidence: 99%
“…For chemical emerging pollutants, Kumar (2013) showed that composting was an effective method for the mineralization and treatment of di-(2-ethyl hexyl) phthalate (DEHP) in sewage sludge that could otherwise be harmful to the environment. The author identified a need for further research to understand the exact mechanism by which organic material is degraded during composting.…”
Section: Enhanced Natural Systemsmentioning
confidence: 99%